Study of amino acid composition of filling for extruded grain crops - U. Ch. Сhomanov; G. E. Zhumalieva; M. Ch Tultabayev; G. S. Aktokalova; R. K. Kassimbek; A. K. Shoman (Алматы технологиялық университетінің хабаршысы, 2021)
In this paper, the amino acid composition of protein filling for extruded grain products is studied. According to research, essential amino acids make up more than 1/3 of all amino acids, which means that the protein filling is of high quality. The article considers covering the daily requirement of amino acids of the body with protein filling. It was found that the protein filling contains a rich amino acid composition, and allows you to get extruded grain products with a long shelf life.